2019
DOI: 10.1371/journal.pone.0213894
|View full text |Cite
|
Sign up to set email alerts
|

Association between social networks and discussions regarding advance care planning among Japanese older adults

Abstract: BackgroundOlder adults’ discussions with family, or with physicians, or with both, about advance care planning (ACP) are increasingly regarded as important for the management of end-of-life care, and yet the factors that induce older adults to engage in ACP discussions are poorly understood. For example, in older adults, is stronger connectedness with family and friends (stronger “networks”) associated with ACP discussions? By facilitating, or by impeding ACP discussions? We sought to evaluate the associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 30 publications
(53 reference statements)
2
18
1
Order By: Relevance
“…A recently published study from a single center in Japan (N = 355) found that weaker social networks (measured by the LSNS‐6) were associated with a lower tendency to have ACP discussions . Prior to the aforementioned study and ours, others have not directly examined the role of social isolation on ACP using nationally representative data .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A recently published study from a single center in Japan (N = 355) found that weaker social networks (measured by the LSNS‐6) were associated with a lower tendency to have ACP discussions . Prior to the aforementioned study and ours, others have not directly examined the role of social isolation on ACP using nationally representative data .…”
Section: Discussionmentioning
confidence: 82%
“…A recently published study from a single center in Japan (N = 355) found that weaker social networks (measured by the LSNS-6) were associated with a lower tendency to have ACP discussions. 24 Prior to the aforementioned study and ours, others have not directly examined the role of social isolation on ACP using nationally representative data. 5,17 Sudore et al reported social isolation explained why older study participants were less likely to engage in discussion with family or friends and suggest that socially isolated individuals may require "special attention and resources".…”
Section: Discussionmentioning
confidence: 91%
“…Micheli et al found that respondents with worse family relations had a higher risk of functional limitations [61]. It is important to develop a network of contacts and build social relations among older persons to arouse their motivation to be active and participate in neighborly assistance [62].…”
Section: Discussionmentioning
confidence: 99%
“…3 Thus, Japanese older adults feel a need to discuss advance care planning to address this discordance. 4 In Japan, the prevalence of discussions approximately doubled from the second half of the 2000s (around 20% in both middle-aged and older adults) 5,6 to the second half of the 2010s (35% in middle-aged adults; 47% in older adults). 7 Although Japan still lacks legislation mandating advance care planning or advance directives, the doubled prevalence is perhaps attributable to rapid growth in the senior population and interest in patient autonomy at end of life.…”
Section: Introductionmentioning
confidence: 99%